Macro-prudential policy on liquidity: What does a DSGE model tell us? - Jagjit S. Chadha; Luisa Corrado (University of Kent, School of Economics, 2011)
The financial crisis has led to the development of an active debate on the use of macro-prudential instruments for regulating the banking system, in particular for liquidity and capital holdings. Within the context of a micro-founded macroeconomic model, we allow commercial banks to choose their optimal mix of assets, apportioning these either to reserves or private sector loans. We examine the implications for quantities, relative non-financial and financial prices from standard macroeconomic shocks alongside hocks to the expected liquidity of banks and to the efficiency of the banking sector. We focus on the response by the monetary sector, in particular the optimal reserve-deposit ratio adopted by commercial banks over the business cycle. Overall we find some rationale for Basel III in providing commercial banks with an incentive to hold a greater stock of liquid assets, such as reserves, but also to provide incentives to increase the cyclical variation in reserves holdings as this acts to limit excessive procyclicality of lending to the private sector.
Keywords: E31; E40; E51; 330; liquidity; interest on reserves; policy instruments; Basel